A formação acadêmica do bacharel em Educação Física no Paraná e sua relação com o campo de atuação profissional - Anversa, Ana Luíza Barbosa (2011)
The objective of this paper research was to examine the professional training of Physical Education-Bachelor in Public Institutions of Parana Upper Education and its relation to the professional performance field. To do so, it was presented initially, historical aspects of the area, particularly the legal implications of recent decades on the initial formation and professional performance field characterization. Relied on the methodology of the descriptive type of feature qualitative, and the technique of data collection semi-structured interview and the use of questionnaires. To conduct the analysis of collected data, it was analyzed the institutional, pedagogical and internship regulation documents of the seven institutions that offer the training in Physical Education Bachelor in parallel to the speeches of the characters and quantitative numbers. The number of 184 subjects were chosen according to their institutional function (seven course coordinators, seven engineers and 170 academic probation trainees). The analysis performed allowed us to draw a picture of the training in the researched institutions, allowing to verify that both university and students realize that the field performance under non-formal is compulsive and requires qualified professionals with skills manifold. It is necessary to go over some points of training, especially the practical approach that are reduced on curricular, or disconnected from each other, resulting in fragmentation of projects in teaching, research and extension and, consequently, the professional formed. The search for a solid and differentiated formation between undergraduate and graduate comes occurring, through research in the area of professional education and intervention and reviews the Institutional Pedagogical Projects, however, the emphasis on content still runs through the first steps. Turning into issues related to mandatory probation, it seems that it is still restricted to traditional areas of activity of the bachelor, as training and health, being necessary to extrapolate these fields to other unexplored or none propagated ones. Moreover, it was noticed that it was necessary more effective intervention of the academic tutors and the field, that this practice can generate a significant learning and not become another bureaucracy to be addressed in formation. Given these points, it is recommended an extension of discussions and studies within the Physical Education Community while training course, State and partner institutions, to promote, interventions active tutoring of academic and teaching in the interventional fields in order to establish a solid and interdisciplinary formation to be effective to the performance field.